Developing as-built BIM model process management system for general contractors: A case study. Issue 5 (3rd July 2016) - Lin, Yu-Cheng; Lee, Hsin-Yun; Yang, I-Tung
Abstract: As the application of building information modeling (BIM) becomes more common, BIM model management becomes necessary and important to enhance the effectiveness of BIM implementation for a general contractor (GC) during the construction phase. Implementation of BIM models in the construction phase, which typically involves participants from different fields, often has numerous BIM-related interfaces and problems. Therefore, feedback from the most recent as-built model tracking and BIM model problems are essential for BIM process management (BIM PM) in the construction field. BIM PM has become the most important aspect of a sound as-built BIM model management strategy. Changes in as-built BIM models should be identified, updated, and tracked for BIM PM, such that version management of as-built BIM models can be improved, while minimizing rework and reducing as-built BIM models development duration. Systematic approaches and information on management platforms for enhancing BIM PM during the construction phase are lacking. This study proposes a novel approach to the BIM model management which is to manage and track all versions of as-built BIM models. The primary purpose of this study is to develop a web Construction BIM-based PM (ConBIM-PM) system to enhance a General Contractor's ability to share BIM PM information and track construction projects more efficiently. The ConBIM-PM system provides users with a centralized storage of all versions of as-built models during the construction phase of a project so that they are able to track and manage the current status of modified as-built models and BIM PM information effectively. Finally, the ConBIM-PM system is applied to a case study of a building project in Taiwan to verify its efficacy and demonstrate its effectiveness. The case study results show that the ConBIM-PM system is effective for BIM PM work by a GC during the construction phase of the BIM implementation.